Impacts of inter cropping on aphid control in a cole crop Brassica oleracae - Vaidya, Kamini; Banskota, Salina (Journal of Natural History Museum, 2008)
Impacts of intercropping upon two insect pest species Lipaphis erysimi and Myzus persicae infecting a cole crop like cauliflower (Brassica oleracae) was studied. Fenugreek (Trigonella foenum-graecum), coriander (Coriandrum sativum) and dill (Anethum gaveolens) were taken as companion plants to maintain diversity. Population of predators like spider were also noted. Population of aphids (Lipaphis erysimi) was found to be least in cole crop inter planted with coriander. Fenugreek came as second that helped in control of aphid. Population of spider was highest in coriander interplanted plot. J. Nat. Hist. Mus. Vol.22, 2005 p.32-37